Risiko sistematis emiten pangan dalam isu krisis pangan - Moses Crespo Lumenta; Chanaya Bertha Ruus (Yayasan Widyantara Nawasena Raharja, 2023)
The issue of the global food crisis since the COVID-19 pandemic is still rife in the Indonesian capital market until early 2023. The purpose of this study is to analyze systematic risk and stock return performance. The sample for this study is stocks in the food sub-sector in Indonesia with an observation period from 1 January 2023 to 30 April 2023. This study finds that the performance of returns on risk is still not optimal for all samples where the average stock returns and systematic risk are still low. Individually, GZCO is a high-risk and return asset and has optimal stock performance.